The moderating role of race/ethnicity and nativity in the relationship between perceived discrimination and overweight and obesity: results from the National Epidemiologic Survey on Alcohol and Related Conditions - Cuevas, Adolfo G. (BMC Public Health, 2019)
BACKGROUND: The overweight/obesity epidemic is a public health issue in the United States (US), that disproportionately affect certain racial/ethnic minority groups. Perceived discrimination has been implicated as a health risk factor. However, research on race/ethnicity, perceived discrimination, and obesity has been mixed. Researchers suggest that perceptions of discrimination may be dependent upon nativity status. This study evaluated the role that nativity status and race/ethnicity play in the relationship between perceived discrimination and overweight/obesity. METHODS: We used Wave 2 of the National Epidemiologic Survey on Alcohol and Related Conditions (2004–2005) [N = 33,319]). Multinomial logistic regression assessed a three-way interaction (perceived discrimination × race/ethnicity × nativity) on overweight and obesity, adjusting for sociodemographic factors and health-related behaviors. RESULTS: The three-way interaction was significant for overweight [F (17, 49) = 3.35; p < 0.001] and obesity [F (17, 49) = 5.05; p < 0.001]. Among US-born individuals, US-born non-Hispanic Blacks had a decreased risk of being obese compared to US-born non-Hispanic Whites at mean levels of perceived discrimination [aRRR = 0.71; 95% CI (0.51–0.98); p = 0.04). Among foreign-born individuals, foreign-born South Americans had an increased risk of being overweight at mean levels of perceived discrimination compared to foreign-born non-Hispanic Whites [aRRR = 8.07; 95% CI (1.68–38.77); p = 0.01], whereas foreign-born Dominicans had a decreased risk of being obese compared to foreign-born non-Hispanic Whites [aRRR = 0.05; 95% CI (0.01–0.20); p < 0.001]. CONCLUSION: Perceived racial discrimination is a risk factor for overweight/obesity for certain groups. Race/ethnicity and nativity may play important roles in the relationship between perceived discrimination and overweight/obesity. Future research is needed to identify the behavioral and psychological pathways that link perceived discrimination and overweight/obesity.